Dermoscopic features of neoplasms in skin of color: A review - Ekene Ezenwa, MD; Jennifer A. Stein, MD, PhD; Loren Krueger, MD (Wolters Kluwer, 2021)
Background: Dermoscopy is undoubtedly a useful tool to improve diagnostic accuracy and minimize the number of unnecessary biopsies. However, much of the literature on dermoscopy focuses on findings in lighter-skin phototypes, leaving potential gaps of knowledge regarding its use in skin of color (SoC). As the clinical applications of dermoscopy continue to increase, understanding dermoscopic patterns in SoC is imperative. Objective: This review discusses the literature on dermoscopic findings of neoplasms in SoC, highlighting unique and characteristic dermoscopic features. Methods: A literature review was performed using the PubMed database. Case reports, case series, case-control studies, and systematic reviews were included. Results: A total of 8326 studies were identified based on the selected search terms, and 41 were included in this review based on relevance. Conclusion: There are specific dermoscopic characteristics in SoC for benign nevi, acral lentiginous melanoma, ethnic melanonychia, and dermatofibroma; however, there is a lack of published data about specific features of cutaneous melanoma, subungual melanoma, pigmented basal cell carcinoma, and pigmented squamous cell carcinoma in SoC. Because pigmented basal cell carcinoma, pigmented squamous cell carcinoma, ethnic melanonychia, and acral lentiginous melanoma are diagnosed at later stages in this population, it is important to understand their dermoscopic features. Further descriptive studies are needed to better characterize unique dermoscopic features in neoplasms in SoC.